A Lagrangian View of Moisture Transport Related to the Heavy Rainfall of July 2020 in Japan: Importance of the Moistening Over the Subtropical Regions. Issue 5 (9th March 2021) - Zhao, N.; Manda, A.; Guo, X.; Kikuchi, K.; Nasuno, T.; Nakano, M.; Zhang, Y.; Wang, B.
Abstract: The transport and accumulation of moisture played an essential role in the extremely heavy rainfall of July 2020 in Japan. To better understand this event in terms of moisture sources and transport routes, backward particle trajectory analysis was conducted. We found two major moisture sources: transport from the tropics and uptake from the subtropics. A narrow moisture channel was found along the edge of the western Pacific Subtropical High (WPSH), transporting the moisture to the Baiu front. However, most moisture from the tropics was lost due to precipitation, and their contributions were reduced to about 15%. In contrast, the subtropical regions contributed over 80% moisture via evaporation and lower tropospheric convection. Among those regions, the western Pacific contributed the most (>33%). This study highlights the role of WPSH in moisture transport and demonstrated the importance of moisture uptake during transport. Plain Language Summary: Heavy rainfalls hit Japan in July 2020, and the related atmospheric river was found to be accumulated by the moisture from tropics and subtropics. The moisture was transported by a narrow moisture channel along the edge of western Pacific Subtropical High. But, due to the precipitation during the transport, the moisture from the tropics decreased. On the other hand, when the air flows passed over the subtropical regions, they were moistened by evaporation and lower troposphere convection. Thus, our results suggest that the moisture from subtropical regions contributed the most to the moisture accumulation during the heavy rain event. Key Points: Moisture came from both the tropical regions and subtropical regions The western Pacific Subtropical High is major forcing of moisture transport and also helped the moistening of low‐level flows Subtropical regions (especially the western Pacific) contributed the most to the moisture accumulation